RAP2.3 negatively regulates nitric oxide biosynthesis and related responses through a rheostat-like mechanism in Arabidopsis - León, José (J Exp Bot, 2020)
Nitric oxide (NO) is sensed through a mechanism involving the degradation of group-VII ERF transcription factors (ERFVIIs) that is mediated by the N-degron pathway. However, the mechanisms regulating NO homeostasis and downstream responses remain mostly unknown. To explore the role of ERFVIIs in regulating NO production and signaling, genome-wide transcriptome analyses were performed on single and multiple erfvii mutants of Arabidopsis following exposure to NO. Transgenic plants overexpressing degradable or non-degradable versions of RAP2.3, one of the five ERFVIIs, were also examined. Enhanced RAP2.3 expression attenuated the changes in the transcriptome upon exposure to NO, and thereby acted as a brake for NO-triggered responses that included the activation of jasmonate and ABA signaling. The expression of non-degradable RAP2.3 attenuated NO biosynthesis in shoots but not in roots, and released the NO-triggered inhibition of hypocotyl and root elongation. In the guard cells of stomata, the control of NO accumulation depended on PRT6-triggered degradation of RAP2.3 more than on RAP2.3 levels. RAP2.3 therefore seemed to work as a molecular rheostat controlling NO homeostasis and signaling. Its function as a brake for NO signaling was released upon NO-triggered PRT6-mediated degradation, thus allowing the inhibition of growth, and the potentiation of jasmonate- and ABA-related signaling.